Answer :
1) Equal the two together (not including the ‘y’)
-x -2 = 4x + 3
2) put x together and the whole number together
* when switching sides, signs ( + & -) changes, watch out for that *
-x - 4x = 3 + 2
-5x = 5 divide by the # with x so you have x
—— ——-
-5. -5
x = -1
therefore, x = -1
For y just plug x into either equation
I’ll use y = 4x + 3
y = 4(-1) + 3
y = -4 + 3
y = -1
therefore, y = -1
-x -2 = 4x + 3
2) put x together and the whole number together
* when switching sides, signs ( + & -) changes, watch out for that *
-x - 4x = 3 + 2
-5x = 5 divide by the # with x so you have x
—— ——-
-5. -5
x = -1
therefore, x = -1
For y just plug x into either equation
I’ll use y = 4x + 3
y = 4(-1) + 3
y = -4 + 3
y = -1
therefore, y = -1